TRAINING ON THE USE OF GOOGLE FORM AS A LEARNING TOOL FOR RENDANG MSMEs IN LUBUK ALUNG - Nurofik, Agus; Sutiyem, Sutiyem; Indrayani, Tri Irfa; Nini, Nini; Merita, Elfi (PT Altin Riset Publishing, 2025)
The purpose of this community service is to provide training in the use of Google Forms as a learning tool for Rendang MSME actors in Lubuk Alung. The method used is the Participatory Rural Appraisal (PRA) method. This method is divided into three stages, namely preparation, implementation, and reflection. The stages of the activity begin with the implementation of several activities: 1) Preparation, including internal coordination activities, carried out by the committee to plan the implementation conceptually, operationally, and job descriptions of each member of the Rendang MSME in Lubuk Alung, determination and recruitment of training participants; 2) Implementation. Starting with the presentation of materials, practical assignments, evaluation, and refinement of Google Form media work by the team; 3) Reflection and Discussion. The location of the training was at LPK AgniCom Lubuk Alung which was attended by all Rendang MSME participants in Lubuk Alung. The results of this training can be concluded that training in the use of Google Forms as a learning medium for Rendang MSME actors in Lubuk Alung is very useful for consumers in providing positive or negative input on the rendang MSME products produced. This can be seen from the results of the questionnaire which shows that the majority of MSME actors (90%) are satisfied with the training which can ultimately provide input from the rendang products produced.